2017
DOI: 10.1021/acs.langmuir.7b00455
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Gas Sensitivity and Sensing Mechanism of Network Structures Assembled from α-Fe2O3 Nanosheets with Exposed {104} Facets

Abstract: Network structures assembled from α-FeO nanosheets with exposed {104} facets were successfully prepared by heating Fe(NO) solution containing polyvinylpyrrolidone (PVP) in air. The α-FeO nanosheet-based network structures demonstrate significantly higher response to ethanol and triethylamine than α-FeO commercial powders. The excellent sensing performances can be ascribed to the exposed (104) facet terminated with Fe atoms. A concept of the unsaturated Fe atoms serving as the sensing reaction active sites is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 46 publications
0
21
0
Order By: Relevance
“…As an important n ‐type semiconductor with bandgap of 2.1 eV, hematite (α‐Fe 2 O 3 ) nanomaterials have attracted considerable attention due to its wide potential applications in many fields, such as magnetic devices, catalytic/photocatalytic fields, pigments, gas sensing, photo anode, and rechargeable lithium‐ion batteries . In recent years, α‐Fe 2 O 3 has been developed as one of the promising gas‐sensing materials due to their nontoxicity, low cost, high chemical stability and high sensitivity , . Increasing attention has been paid to rationally engineer the shape and exposed crystallographic facets of α‐Fe 2 O 3 nanocrystals to shed light on the relationship between the performance and structure.…”
Section: Introductionmentioning
confidence: 99%
“…As an important n ‐type semiconductor with bandgap of 2.1 eV, hematite (α‐Fe 2 O 3 ) nanomaterials have attracted considerable attention due to its wide potential applications in many fields, such as magnetic devices, catalytic/photocatalytic fields, pigments, gas sensing, photo anode, and rechargeable lithium‐ion batteries . In recent years, α‐Fe 2 O 3 has been developed as one of the promising gas‐sensing materials due to their nontoxicity, low cost, high chemical stability and high sensitivity , . Increasing attention has been paid to rationally engineer the shape and exposed crystallographic facets of α‐Fe 2 O 3 nanocrystals to shed light on the relationship between the performance and structure.…”
Section: Introductionmentioning
confidence: 99%
“…Plenty of work has conrmed that the {012} and {104} planes of a-Fe 2 O 3 are high-index planes. [31][32][33][34] Ma et al found that the exposed {104} planes of a-Fe 2 O 3 exhibits excellent gas sensing properties. 33 Zhao et al investigated that a-Fe 2 O 3 nanocubes exposed {012} active facets combination with graphene lead to boosted lithium storage capability.…”
Section: Introductionmentioning
confidence: 99%
“…[31][32][33][34] Ma et al found that the exposed {104} planes of a-Fe 2 O 3 exhibits excellent gas sensing properties. 33 Zhao et al investigated that a-Fe 2 O 3 nanocubes exposed {012} active facets combination with graphene lead to boosted lithium storage capability. 34 Recently, Xiang and coworkers reported that a-Fe 2 O 3 nanocubes with {012} facets have much higher photocatalytic water oxidation activity than a-Fe 2 O 3 nanoakes with {001} facets.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Hematite (α-Fe 2 O 3 ), an important part of the iron oxide materials, is the most stable metal oxide with favorable optical band gap (about 2.06 eV). 7 The α-Fe 2 O 3 has been widely applied in photoelectrocatalytic water splitting, 8 environmental remediation, 9 sensor, 10 antimicrobial agents, 11 etc., due to its abundance, good stability, nontoxicity, and low cost. [7][8][9][10][11][12] The micro-or nano-biotemplate preparation of iron oxide was rarely reported.…”
Section: Introductionmentioning
confidence: 99%
“…7 The α-Fe 2 O 3 has been widely applied in photoelectrocatalytic water splitting, 8 environmental remediation, 9 sensor, 10 antimicrobial agents, 11 etc., due to its abundance, good stability, nontoxicity, and low cost. [7][8][9][10][11][12] The micro-or nano-biotemplate preparation of iron oxide was rarely reported. In this paper, the cotton was used as biological template with impregnation adsorbed with Fe 3+ and by drying and calcination, and then the excellent bionic hierarchical fibers iron oxide has been prepared and the performance has been further studied.…”
Section: Introductionmentioning
confidence: 99%